Detection of Subclinical Mastitis in Dairy Cows using California Mastitis Test and Udder Pathogen - Evi Nur Qolbaini; I Made Artika; Dodi Safari (Current Biochemistry, 2014)
Subclinical mastitis is an infection of the udder devoid of clinical symptoms, bacteria are one of the causes behind this disease. In the present study, we investigated subclinical mastitis in dairy cows using the California mastitis test (CMT) and udder pathogens from KUNAK (Kawasan Usaha Peternak Sapi Perah) Cibungbulang, Bogor, West Java, Indonesia. We randomly collected 102 milk samples from dairy farms in different stalls. We found that 87 out of the 102 (86 %) milk samples were positive for CMT test with level+1, level+2, and level+3 were 22 %, 45 %, and 33 % respectively. We also identified three different major bacterial groups: staphylococcus, streptococcus, and enterobacteria based on gram staining, oxidase test, and coagulase test. It can be concluded that the case of bovine subclinical mastitis in Kunak Bogor was very high and caused by various bacteria which infected cows.